(untitled) (Journal of Information Technologies in Education (ITE), 2012)
An approach to the organization of the technical support in the establishments of higher education with the help of a special information system is regarded in the article. The problems, which will be solved with the support system, are revealed. The most famous open-source systems that use the service-oriented architecture are examined. Advantages and disadvantages of the system are shown.